Evaluation of the Application of the Interpretation of Financial Accounting Standard Number 35 on the Preparation of Financial Statements of Non-Profit Oriented Entities at the Hermon Tolombukan Child Development Center - Owu, Ribka Yuliana Syaloom; Tinangon, Jantje J.; Wangkar, Anneke (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to evaluate how the Interpretation of Financial Accounting Standards (ISAK) Number 35 is applied in the preparation of financial statements of the Hermon Tolombukan Child Development Center. The purpose of this interpretation is to increase the transparency and accountability of the financial statements of non-profit-oriented entities. ISAK No. 35 is an accounting guideline for non-profit entities, which includes reporting of activities, balance sheets, cash flows, and changes in net assets. This study uses a qualitative descriptive method with a case study approach to identify the extent to which the Hermon Tolombukan Child Development Center has implemented ISAK No. 35 in the preparation of its financial statements. Data was obtained through interviews, documentation, and direct observation of the financial report preparation process. The results of the study show that the application of ISAK Number 35 to the existing PPA is not in accordance with the existing accounting standards. This study recommends the need for further training for financial managers and periodic evaluations to ensure that accounting standards are applied consistently and effectively. With this evaluation, it is hoped that the update of the financial recording system can be improved, and further technical evaluation is expected to help ensure that the implementation of ISAK No. 35 can be implemented comprehensively.